A manager/researcher can learn about professional practices in their workplace by using case research. Issue 1 (13th February 2017) - Morelli, Joseph; Perry, Chad
Abstract : Purpose: The research involved a funeral home manager who used case research within another funeral home to learn more about how to manage his own workplace. This research aims to investigate for the first time how funeral homes can strategically manage the marketing of their services to customers during emotional times in their lives. Design/methodology/approach: The two methodologies of convergent interviewing and case research in a funeral home workplace are described in detail. Findings: The case research revealed what strategic marketing management principles have to be emphasized in the unique context of funeral homes, and the related need to develop a hybrid strategy. The project demonstrated that a case research project can align a formal research project with the professional development of managers. Practical implications: The paper provided the first author with a valuable learning experience of management in his industry, and provides other funeral home managers with a detailed guide to doing their strategic marketing management. Originality/value: The authors' contributions are the first example of case research used for workplace learning in a blend of formal academic research and workplace learning. It is also the first academically rigorous coverage of strategic marketing management workplace practices in the unique context of funeral homes; they were uncovered in interviews across a range of staff levels in a funeral home.